Peningkatan Derajat Kesehatan Siswa SD 11 Kesiman Denpasar melalui Perilaku Hidup Bersih dan Sehat - I Gusti Ayu Putu Satya Laksmi; Niken Ayu Merna Eka Sari; Putu Ayu Parwati; Ni Komang Ayu Resiyanthi; Ni Luh Gede Intan Saraswati (Jurnal Empathy Pengabdian Kepada Masyarakat, 2020)
Background: PHBS at school age that is not good enough will cause various diseases such as diarrhea, toothache, skin pain and worms. Thus, to reduce the prevalence of these bad impacts, it is important to apply PHBS. Methods: The method used is the lecture method. The team conducted health education related to Clean and Healthy Lifestyle, brushing teeth together, and examining faeces for worms. Results: there were 6 students' worms found, there were 10 students who had not brushed their teeth at night, all students listened well to the material that the team conveyed. Conclusion: Problem solving that can be done is by providing knowledge, understanding through counseling about PHBS.